# How do you solve 6x = 4x - ( - 18)?

Jun 9, 2018

$x = 9$

#### Explanation:

Simplify first as follows:

$6 x = 4 x - \left(- 18\right)$

$6 x = 4 x + 18$-----> opening the bracket

$6 x - 4 x = 4 x - 4 x + 18$ -----> subtracting $4 x$ both sides

$2 x = 18$

$x = \frac{18}{2}$

$x = 9$

$6 \left(9\right) = 4 \left(9\right) - \left(- 18\right)$

$54 = 36 + 18$ ----> Correct!

Jun 9, 2018

$x = 9$

#### Explanation:

$\text{note that } - \left(- 18\right) = + 18$

$6 x = 4 x + 18$

$\text{subtract "4x" from both sides}$

$2 x = 18$

$\text{divide both sides by 2}$

$x = \frac{18}{2} = 9$

$\textcolor{b l u e}{\text{As a check}}$

Substitute this value into the equation and if both sides are equal then it is the solution.

$\text{left side } = 6 \times 9 = 54$

$\text{right side } = \left(4 \times 9\right) + 18 = 36 + 18 = 54$

$x = 9 \text{ is the solution}$

Jun 9, 2018

$x = 9$

#### Explanation:

$6 x \textcolor{red}{=} 4 x - \left(- 18\right)$ | you start with this

$6 x \textcolor{red}{=} 4 x - \left(- 18\right)$ | you put the '4x' on the other side
$6 x - 4 x \textcolor{red}{=} - \left(- 18\right)$
$2 x \textcolor{red}{=} - \left(- 18\right)$

$2 x \textcolor{red}{=} - \left(- 18\right)$ | -1 times -8
$2 x \textcolor{red}{=} - 1 \left(- 18\right)$
$2 x \textcolor{red}{=} 18$

$2 x \textcolor{red}{=} 18$ | put the 2 to the other side
$x \textcolor{red}{=} \frac{18}{2}$
$x \textcolor{red}{=} 9$